2096. Evaluation of a Midline Catheter Program and Effect on Central Line-Associated Blood Stream Infections. (26th November 2018) - Hankins, Richard; Rupp, Mark E; Micheels, Teresa; Sy, Adrienne; Boesch, Angela; Hayes, Kim; Evans, Luana; Cawcutt, Kelly
Abstract: Background: Central line-associated blood stream infections (CLABSI) result in increased patient morbidity. Guidelines recommend against peripheral venous catheters when access is required for longer than 6 days, often leading to central venous catheter (CVCs) placement. To improve vascular access device choice and reduce the potential risk of CLABSIs, we implemented a quality improvement initiative compromised of a new vascular access algorithm with introduction of midline utilization and sought to evaluate the impact of midline use on CLABSI rates. Methods: A prospective quality improvement assessment from October 2017 through March 2018 analyzed the infection rates of midline catheters and CVCs. When a consult was placed for a peripherally inserted central catheter (PICC) that the patient would be evaluated via the vascular access algorithm (Figure 1) for whether they should receive a midline catheter, a PICC or a traditional CVC. The midline catheters, PICCs, and CVCs were monitored for duration of indwell and bloodstream infections consistent with reportable CLABSI definitions. Results: In the month prior to implementation, the institutional CLABSI rate was 1.36 per 1, 000 CVC (including PICC) days. Since October 2017, there have been 4, 588 midline catheter days, with two midline infections, for a cumulative rate over those 6 months of 0.435 midline catheter infections per 1, 000 midline days. This was compared with 26, 575 CVC days, with 33 documented CLABSIs, for a rate of 1.242 per 1, 000 CVC days. Since the vascular algorithm was implemented, the infection rate from the compilation of CVC and midline catheters is 1.12 per 1, 000 catheter days. Conclusion: The implementation of a vascular access algorithm including midlines may effectively reduce central line insertions and thereby decrease CLABSIs through appropriate utilization of a lower risk device (midline). Further research into comparing additional risks, benefits, complications and costs of midline catheters and all styles of central venous catheters is warranted. Disclosures: All authors: No reported disclosures.